Utilization of Household Waste into Compost at Radhiyatan Mardhiyah Senior Citizen Home in Batu City (Fakultas Teknik, Universitas Brawijaya, 2025)
Radhiyatan Mardhiyyah Elderly Care Center is a Muslimat NU institution located in Jl. Lesti Utara Gg. Makam, Ngaglik, Batu District, was inaugurated by the Indonesian Minister of Social Affairs, Khofifah Indar Parawansa, in 2017. Nursing homes serve as residences for elderly individuals who require special care and a clean, healthy environment. The increasing number of residents in such facilities contributes to the growing volume of household waste, making proper waste management a vital aspect in maintaining environmental hygiene and supporting the health and comfort of the elderly. This community service activity aimed to address this issue by providing education on waste segregation and practical training on crafting from waste materials. The activities involved lecturers, students, and elderly residents as partners. The implementation was carried out through several stages: site survey and delivery of materials on simple waste management. The activity's success was evaluated based on the satisfaction level indicated by the questionnaire results. This community service activity has successfully assisted the care center in maintaining cleanliness and the health of its elderly residents.